PENGARUH LATAR BELAKANG TINGKAT PENDIDIKAN ORANGTUA TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS III SDN SAMBIREJO 01 KOTA SEMARANG - Mila, Febriana Jamiatul; Baedowi, Sunan; Mudzanatun, Mudzanatun (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
Parents as the main educators for their children must have extensive experience and insight to produce the next generation of quality and good morals. The high level of parental education will affect parenting styles, insights, and ways of educating children which will influence in providing guidance and direction to achieve a future with good learning outcomes. The purpose of this study was to determine the effect of the background level of parental education on the learning outcomes of Islamic Religious Education in grade III B SD Negeri Sambirejo 01 Semarang City. This type of research is a quantitative study using the Ex-Post facto type with a survey research design. The samples taken were 34 students of class III B SD Negeri Sambirejo 01 Semarang City. The data in this study were obtained through questionnaires, interviews, and documentation. The results showed that the background level of parental education has a positive correlation with the learning outcomes of Islamic Religious Education as evidenced by the product-moment hypothesis test analysis. The analytical method used is a simple linear regression with the result of tcount 9.384 with a significanceof 0.000 <0.05. This result shows that tcount is significant so that Ho is rejected and Ha is accepted, which means "There is a significant influence between the background of the level of parental education on the learning outcomes of Islamic Education for grade III B students of SDN Sambirejo 01 Semarang City for the 2018/2019 academic year". With the coefficient of determination (R2) of 0.740 = 74% and the remaining 26% is influenced by other factors.